Perancangan Media Promosi Produk UMKM Berbasis Openchart di Kabupaten Padang Lawas Utara - ritonga, Lannihara; Annas, Firdaus; Wulandari, Putri (Yayasan Lembaga Studi Makwa, 2024)
This article discusses the design of promotional media for micro, small and medium enterprise (MSME) products in North Padang Lawas by utilizing the OpenChart platform. In the digital era, the existence of effective promotional media is very important to increase the visibility and competitiveness of MSME products. This research identifies the problems faced by MSMEs to promote products online and explores the potential of OpenChart as a user-friendly and efficient solution. The method used in the research is R & D research, which includes needs analysis, prototyping and usability testing. The result of this design is the creation of an OpenChart-based MSME product promotion media in the North Padang Lawas district. Also this promotional media can be utilized in people's lives around the world. It can also expand market reach and can increase sales. And also the success of the promotion of MSME products in North Padang Lawas district. Thus this research can be expected to be a reference for other MSMEs and policy guides in increasing product competitiveness through the use of information technology. The purpose of this research is to produce OpenChart-based MSME product promotion media in North Padang Lawas district. This research involves training MSME players about OpenChart, developing attractive marketing content, as well as data analysis, sales, and promotion to the community in the district.